Stoichiometry of G protein subunits affects the Saccharomyces cerevisiae mating pheromone signal transduction pathway. - Cole, G M (1990)
The Saccharomyces cerevisiae GPA1, STE4, and STE18 genes encode products homologous to mammalian G-protein alpha, beta, and gamma subunits, respectively. All three genes function in the transduction of the signal generated by mating pheromone in haploid cells. To characterize more completely the role of these genes in mating, we have conditionally overexpressed GPA1, STE4, and STE18, using the galactose-inducible GAL1 promoter. Overexpression of STE4 alone, or STE4 together with STE18, generated a response in haploid cells suggestive of pheromone signal transduction: arrest in G1 of the cell cycle, formation of cellular projections, and induction of the pheromone-inducible transcript FUS1 25- to 70-fold. High-level STE18 expression alone had none of these effects, nor did overexpression of STE4 in a MATa/alpha diploid. However, STE18 was essential for the response, since overexpression of STE4 was unable to activate a response in a ste18 null strain. GPA1 hyperexpression suppressed the phenotype of STE4 overexpression. In addition, cells that overexpressed GPA1 were more resistant to pheromone and recovered more quickly from pheromone than did wild-type cells, which suggests that GPA1 may function in an adaptation response to pheromone.